2020
DOI: 10.1177/0973801020904490
|View full text |Cite
|
Sign up to set email alerts
|

Access to Credit, Farm Productivity and Market Participation in Ghana: A Conditional Mixed Process Approach

Abstract: This study tests the hypothesis of whether credit impacts productivity, and whether productivity in turn impacts market participation under a simultaneous modelling framework of credit, productivity and market participation, which has not been pursued in the literature. Using data from the Ghana Living Standards Survey Round 6, we applied a conditional mixed process estimation technique to correct for selectivity bias and unobserved endogeneity. We find that credit positively impacts productivity, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…It can also be used to hire labor and farm managers to work on the cocoa farm, which assists in the creation of jobs in rural settings. This finding goes in line with the studies by Alhassan et al (2020), which indicated that credit access is key in the participation of individuals in agricultural activities. For non-cocoa enterprises, various inputs and necessary investments can be done with these capital.…”
Section: Determinants Of Participation In Cocoa and Non-cocoa Enterpr...supporting
confidence: 91%
“…It can also be used to hire labor and farm managers to work on the cocoa farm, which assists in the creation of jobs in rural settings. This finding goes in line with the studies by Alhassan et al (2020), which indicated that credit access is key in the participation of individuals in agricultural activities. For non-cocoa enterprises, various inputs and necessary investments can be done with these capital.…”
Section: Determinants Of Participation In Cocoa and Non-cocoa Enterpr...supporting
confidence: 91%
“…This result provides an information to suggest that the development of industrial sector in the country has not taken the agricultural sector into consideration, hence the negative relationship between the two. Moreover, urbanisation reduces agricultural development in Ghana which is in line with Malik and Ali (2015) while as argued by Alhassan et al (2020), financial development is found to increase Ghana's agricultural development.…”
Section: Results Of Effects Of Aggregate Carbon Emissions On Agricult...mentioning
confidence: 61%
“…farmers). As established byAlhassan et al (2020), access to credit by farmers boost their liquidity status, which promotes investment in farm enterprises via adoption of improved technology, which in turn, propels agricultural development. The effect of industrialisation on agricultural development is mixed.…”
mentioning
confidence: 99%
“…Finally, contrary to the national network, micro and macro lenders and agents focused on energy supply were not identified in the regional network as important in affecting the SSIT diffusion process. Much has been written of the paucity of access to affordable finance in Ghana (Alhassan et al 2020;FAO and IFC, 2014;Quartey et al 2012), which might be reflected in the perceived importance of this sector at the national level, as well as the lack of influence of this sector in driving current diffusion processes on the ground, given its continued absence in northern Ghana.…”
Section: Discussionmentioning
confidence: 99%